The management and implementation of School Sport Mass Participation Programme (SSMPP) in selected secondary schools at Malamulele East Education Cluster in the Limppopo Province - Mathebula, Nkhensani Stella (University of Limpopo, 2015)
Recent changes in the Department of Sport and Recreation have placed new external pressures and challenges on Sport officials to change their ways of managing School Sport Mass Participation Programme in their sphere of operation. The above challenge prompted the researcher to investigate the Management and Implementation of School Sport Mass Participation Programme (SMPP) in selected secondary schools at Malamulele East Education Cluster in the Limpopo Province. The study is concerned with the development of effective strategies that will enhance the capacity of sport officials and change their perception; and that of other stakeholders on the management and implementation of the School Sport Mass Participation Programme. This study used the context of Malamulele East cluster as its spring board in engaging in the daunting subject of the School Sport Mass Participation Programme. Surely, with all the changes that are involved in the implementation of the above programme, there is a need to review the way the School Sport Mass Participation Programme should be implemented, hence this study. The literature review established the relationship between Sport Management and the implementation of School Sport Mass Participation Programme. In this regard, the study showed that managers who apply the principles of management, motivation, participation in decision making, management by objectives and delegation can enhance the management and implementation of School Sport Mass Participation Programme in the area of the study. In this study, a mixed research design approach was employed to investigate the factors that promote and hinder the management and implementation of the School Sport Mass Participation Programme in Malamulele East cluster. Both questionnaires and structured interviews were employed to collect data from the respondents. The main findings of the study confirmed that there are challenges associated with the management and implementation of the School Sport Mass Participation Programme in Malamulele East cluster. Challenges such as lack of managerial skills, clear delegation of powers, lack of clarity on policy guidelines, inadequate resources, lack of cooperation vi and shortage of financial resources hampered the successful implementation of the School Sport Mass Participation Programme in Malamulele. In conclusion, the study also led to suggestions of strategies and recommendations that can improve the management and implementation of School Sport Mass Participation Programme in Malamulele East Education Cluster in the Limpopo Province.
Thesis (M. Dev.) -- University of Limpopo, 2015
Keywords: School sports; Management of school sports programmes; Sports officials; Development of effective strategies; School sports